2010
DOI: 10.1007/s10533-009-9401-1
|View full text |Cite
|
Sign up to set email alerts
|

Variable flushing mechanisms and landscape structure control stream DOC export during snowmelt in a set of nested catchments

Abstract: Stream DOC dynamics during snowmelt have been the focus of much research, and numerous DOC mobilization and delivery mechanisms from riparian and upland areas have been proposed. However, landscape structure controls on DOC export from riparian and upland landscape elements remains poorly understood. We investigated stream and groundwater DOC dynamics across three transects and seven adjacent but diverse catchments with a range of landscape characteristics during snowmelt (April 15-July 15) in the northern Roc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
102
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(108 citation statements)
references
References 40 publications
4
102
2
Order By: Relevance
“…Knowledge of runoff source areas and how they change through time is critical for deciphering water quantity and composition signals measured at the watershed outlet. For example, the transport of DOC to the stream network [e.g., McGlynn and McDonnell, 2003b;Pacific et al, 2010] greatly depends on the spatial extent of contributing areas and the intersection of DOC accumulation and connectivity-driven mobilization of DOC to streams. Temporally dynamic streamflow and composition source areas can change in time, even on individual rain event time scales, and may partially explain observed streamflow solute behavior across a range of systems including but not limited to TCEF.…”
Section: Variable Contributing Areamentioning
confidence: 99%
“…Knowledge of runoff source areas and how they change through time is critical for deciphering water quantity and composition signals measured at the watershed outlet. For example, the transport of DOC to the stream network [e.g., McGlynn and McDonnell, 2003b;Pacific et al, 2010] greatly depends on the spatial extent of contributing areas and the intersection of DOC accumulation and connectivity-driven mobilization of DOC to streams. Temporally dynamic streamflow and composition source areas can change in time, even on individual rain event time scales, and may partially explain observed streamflow solute behavior across a range of systems including but not limited to TCEF.…”
Section: Variable Contributing Areamentioning
confidence: 99%
“…Yet, the difference in the annual hydrological export of DOC between the two catchments was small (<2 %), evidencing the limited capacity of this riparian forest to supply DOC to the stream. Recently, Pacific et al (2010) concluded that riparian systems have an impact on annual stream DOC export only when there is a significant riparian-to-hillslope area ratio (at least 5 %). Concordantly, our results indicated that the FSW riparian forest (2 % of the catchment area) was too small to modify annual stream DOC export in this semiarid catchment.…”
Section: Riparian Vegetation As a Source Of Dissolved Organic Matter mentioning
confidence: 99%
“…There is a large flux of dissolved organic carbon (DOC) from riparian soils to stream ecosystems (e.g. Seibert et al, 2009;Hornberger et al, 1994), and this source of organic matter can contribute considerably to the annual export of DOC at the catchment scale (Inamdar and Mitchell, 2006;Pacific et al, 2010). At the same time, riparian zones can act as important sinks of essential nutrients such as nitrate, substantially reducing nitrate export from catchments (Peterjohn and Correll, 1984;Hill, 1996;Vidon et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the global relevance of increasing river nutrient concentrations, there is a critical need to develop a thorough mechanistic understanding of the variability and controls on nutrient mobilization and export from river catchments. In particular, identification of the dominant landscape source zones that contribute to nutrient export is often challenging [Bishop et al, 1994;Pacific et al, 2010;Grabs et al, 2012], despite the importance of this for their effective management.…”
Section: Introductionmentioning
confidence: 99%